Towards a General Definition of Modeling - Podnieks, Karlis (My University, 2010)
What is a model? Surprisingly, in philosophical texts, this question is asked (sometimes), but almost never – answered. Instead of a general answer, usually, some classification of models is considered. The broadest possible definition of modeling could sound as follows: a model is anything that is (or could be) used, for some purpose, in place of something else. If the purpose is “answering questions”, then one has a cognitive model. Could such a broad definition be useful? Isn't it empty? Can one derive useful consequences from it? I'm trying to show that there is a lot of them.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; models; modeling; model template; Dappled World